Avaliação das propriedades ópticas do leite como metodologia para detecção de adulteração - Paiva, Larissa Silva (2019)
Milk is one of the most widely consumed foods in the world. In this sense, it must always ensure the preservation of its sensorial, nutritional and safety characteristics, which are increasingly important requirements for the consumer, the industry and, consequently, the producer. Thus, it is essential the regularity of product quality, which is currently done by routine analyses and previously regulated analyses, aiming to verify the occurrence of possible irregularities. These analyses are done from obtaining raw milk, processing and distributing the final product. However, with the intense number of frauds and new procedures to circumvent the minimum quality parameters, it is necessary to establish new methodologies to accelerate this process of detecting milk adulteration. Thus, this study evaluated a new methodology for detecting adulteration in milk, through the use of the integrating sphere that was able to generate data from the optical properties of the product, such as absorption coefficient and reduced light scattering for comparisons with the characteristic values for each milk. The results in the wavelength determined from 575.1 nm, revealed both for commercial milk and raw milk, small variations of the attenuation coefficient (µe) when the product was adulterated by water and hydrogen peroxide. Caustic soda presented accentuated variations, which indicated easily evidence of fraud. The cheese whey was the most complex adulterant to evaluate, because it did not cause significant variations, needing a more thorough study. Finally, it was a very promising methodology that, once improved, could be inserted in the future routine practices for fraud detection.